Diverse dystonin gene mutations cause distinct patterns of Dst isoform deficiency and phenotypic heterogeneity in Dystonia musculorum mice - Nozomu Yoshioka; Yudai Kabata; Momona Kuriyama; Norihisa Bizen; Li Zhou; Dang M. Tran; Masato Yano; Atsushi Yoshiki; Tatsuo Ushiki; Thomas J. Sproule; Riichiro Abe; Hirohide Takebayashi (The Company of Biologists, 2020)
Loss-of-function mutations in dystonin (DST) can cause hereditary sensory and autonomic neuropathy type 6 (HSAN-VI) or epidermolysis bullosa simplex (EBS). Recently, DST-related diseases were recognized to be more complex than previously thought because a patient exhibited both neurological and skin manifestations, whereas others display only one or the other. A single DST locus produces at least three major DST isoforms: DST-a (neuronal isoform), DST-b (muscular isoform) and DST-e (epithelial isoform). Dystonia musculorum (dt) mice, which have mutations in Dst, were originally identified as spontaneous mutants displaying neurological phenotypes. To reveal the mechanisms underlying the phenotypic heterogeneity of DST-related diseases, we investigated two mutant strains with different mutations: a spontaneous Dst mutant (Dstdt-23Rbrc mice) and a gene-trap mutant (DstGt mice). The Dstdt-23Rbrc allele possesses a nonsense mutation in an exon shared by all Dst isoforms. The DstGt allele is predicted to inactivate Dst-a and Dst-b isoforms but not Dst-e. There was a decrease in the levels of Dst-a mRNA in the neural tissue of both Dstdt-23Rbrc and DstGt homozygotes. Loss of sensory and autonomic nerve ends in the skin was observed in both Dstdt-23Rbrc and DstGt mice at postnatal stages. In contrast, Dst-e mRNA expression was reduced in the skin of Dstdt-23Rbrc mice but not in DstGt mice. Expression levels of Dst proteins in neural and cutaneous tissues correlated with Dst mRNAs. Because Dst-e encodes a structural protein in hemidesmosomes (HDs), we performed transmission electron microscopy. Lack of inner plaques and loss of keratin filament invasions underneath the HDs were observed in the basal keratinocytes of Dstdt-23Rbrc mice but not in those of DstGt mice; thus, the distinct phenotype of the skin of Dstdt-23Rbrc mice could be because of failure of Dst-e expression. These results indicate that distinct mutations within the Dst locus can cause different loss-of-function patterns among Dst isoforms, which accounts for the heterogeneous neural and skin phenotypes in dt mice and DST-related diseases.